Unipolar resistive switching behavior in sol–gel synthesized FeSrTiO3 thin films. Issue 85 (24th November 2017) - Thakre, Atul; Kaswan, Jyoti; Shukla, A. K.; Kumar, Ashok
Abstract : A robust and reproducible resistance switching in iron substituted strontium titanate is reported which shows giant high to low resistance state ratio (∼10 5 ) and stable charge retention. Abstract : A robust unipolar resistive switching (URS) was successfully observed in sol–gel derived perovskite type Fe-doped strontium titanate (FeSTO) thin films, deposited on an ITO-coated glass substrate by a spin-coating technique. The surface topography of the films was characterized by atomic force microscopy that suggested a smooth surface with an average surface roughness nearly 1–2 nm. The crystal structure, URS phenomena, current–voltage characteristics, and dielectric and impedance behavior were analyzed for both high resistance state (HRS) and low resistance state (LRS). The X-ray photoelectron spectroscopy (XPS) was also employed to investigate the valence states of the host and dopants elements. The Au/FeSTO/ITO device offers a large resistance ratio of HRS and LRS ( R off / R on ) around 10 5, long stable retention characteristics for 10 4 s, and a distinguished and large non-overlapping voltage window of ∼4 to 6 V for SET and RESET operations.